Fantastic: breviary - Iannace, Ricardo (Revista USP, 2024)
This breviary explores unusual narratives in which they have dominant characteristics of the fantastic. To this end, tales from the surprising tradition are revisited, such as “The sandman” and “House taken over”. The objective is to recognize elements and structural aspects of this lineage of intrigues, aiming at the articulation – through specific excerpts – with essays that, for decades, have investigated this fiction linked to the phenomenon of the double, to the hesitant reception, to the man immersed in a kaleidoscope of uncertainties.